PERANAN GOOD CORPORATE GOVERNANCE UNTUK MEMINIMALISASI TINDAKAN CREATIVE ACCOUNTING PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Indah Oktari Wijayanti; Dri Asmawanti S (UNIB Press, 2017)
This study aims to examine the influence of the role of good corporate governance to minimize creative accounting actions in manufacturing companies listed on the Indonesian stock exchange (BEI) in 2015-2017. The variables tested in this study consisted of institutional ownership and managerial ownership and creative accounting in proxy with earnings management as measured by discretionary accruals estimated using the modified Jones model (1995). The sample of this study is a manufacturing company listed on the Stock Exchange in 2013-2017. This study uses purposive sampling method in determining the number of samples used and obtained 77 companies used as samples. Multiple regression models and descriptive statistics are used for data analysis. The results show that corporate governance mechanisms that are proxied by institutional ownership and managerial ownership do not affect earnings management.Keywords: institutional ownership, managerial ownership, creative accounting.